32-bit low-delay arithmetic-logic unit - Mu, Yihao (Nanyang Technological University, 2022)
ALU is a combinational digital circuit that performs arithmetic and bitwise operations on integer binary numbers. For example, integer add, substrate, logic and, logic or and shift operation. ALU is also a fundamental component of computing circuits, especially the CPU in computers. The improvement of ALU is an essential topic in modern CPU design history because it is one factor that restricts the frequency of the CPU. A 32-bits high-speed ALU is proposed in this dissertation, and several techniques are combined to improve its performance. CLA is designed to improve the speed of the ALU. Complementary code extends the computational area from natural numbers to integers. A reusable adder is designed to reduce area. Overflow is computed to prevent data error and loss. After using Verilog to build the ALU, the simulation and synthesis are also done with the help of tools such as Design Compiler and Verilog Compiled Simulator, using AMS 0.35um library. The result shows that the 32-bits high-speed ALU leads to 50.4% improvement in delay compared with the benchmarked design.